Caso de estudio: impacto del desarrollo de la publicidad digital en la planificación de medios - Serrano Arias, Daniela (2023)
Advertising is undergoing a transformation due to the development of digital media. The advertising and media industry must adapt to the changes generated by the accelerated digitalization. By providing greater segmentation, personalization, interactivity, measurement and creativity, it has altered the work processes of media agencies and specifically, for media planners, it has presented new challenges. Three major challenges are identified: audience fragmentation, platform proliferation and the measurement and attribution of results. The responsibilities of the media professional are expanded by integrating traditional media strategies with digital media. Media convergence is an important point as off media are growing in the digital environment. Finally, it is concluded that professionals with profiles oriented to the development of technological, analytical and strategic competencies are required. Media agencies have the task of encouraging the updating of this knowledge and also provide constant training.